2018
DOI: 10.2319/072717-498.1
|View full text |Cite
|
Sign up to set email alerts
|

Ribbon-wise customized lingual appliance and orthodontic anchor screw for the treatment of skeletal high-angle maxillary protrusion without bowing effect

Abstract: This case report demonstrates the treatment of a skeletal Class II high-angle adult patient with bimaxillary protrusion, angle Class I occlusion, and crowded anterior teeth. A ribbon-wise arch wire and a customized lingual appliance with anterior vertical slots were used to achieve proper torque control of the maxillary anterior teeth. An orthodontic anchor screw and a palatal bar were used for vertical control to avoid increasing the Frankfort-mandibular plane angle (FMA) by maxillary molar extrusion. Through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…A greater height tended to enlarge the moment of inertia and provide more rigid support to the occlusal plane. To our knowledge, only Inami et al reported a minimum vertical bowing effect with a ribbonwise lingual appliance [ 28 ]. However, they also remarked on insufficient control of the ribbon wire in lingual tipping due to the thinner geometry, and a palatal bar was needed to keep the tooth upright.…”
Section: Discussionmentioning
confidence: 99%
“…A greater height tended to enlarge the moment of inertia and provide more rigid support to the occlusal plane. To our knowledge, only Inami et al reported a minimum vertical bowing effect with a ribbonwise lingual appliance [ 28 ]. However, they also remarked on insufficient control of the ribbon wire in lingual tipping due to the thinner geometry, and a palatal bar was needed to keep the tooth upright.…”
Section: Discussionmentioning
confidence: 99%
“…The greater height would enlarge the moment of inertia and provide more rigid support to the occlusal plane. To our knowledge, only Inami et al reported a minimum vertical bowing effect with a ribbon-wise lingual appliance [23]. However, they also pointed to insu cient control of the ribbon wire in lingual tipping due to the thinner geometry, and the palatal bar was needed to keep the tooth upright.…”
Section: Discussionmentioning
confidence: 92%
“… Reduction of the incidence of decalcification with its inherent savings in terms of enamel and financial burden (see discussion below), 20 Individualized treatment plans that can be predictably transferred to the patients' mouth, 21 Better torque control because of precise slot and arch wires dimensions, 22 Biomechanical advantages in terms of vertical control thanks to ribbon‐arch wires, 23 and Avoidance of secondary effects due to conventional non‐customized orthodontic treatment …”
Section: Why Lingual Orthodontics?mentioning
confidence: 99%
“…The use of customized and indirectly bonded braces minimizes errors in bracket positioning F I G U R E 5 Based on the patient's smile and facial esthetics the desired change in incisor exposure, angulation and alignment of the incisors is incorporated into the setup that will be the blueprint for appliance design and fabrication. Note the correction of the angulation of the midline and the relative extrusion of the upper incisors relative to the back teeth • Better torque control because of precise slot and arch wires dimensions, 22 • Biomechanical advantages in terms of vertical control thanks to ribbon-arch wires, 23 and • Avoidance of secondary effects due to conventional non-customized orthodontic treatment Human-error present in direct bonding techniques, 14 Inter-patient variability not accounted for with non-customized appliances, 24 and No preservation of arch form.…”
Section: Why Lingual Orthodontics?mentioning
confidence: 99%